الاختناق حول الولادة - ديوب عدنان; خوري مها; محمود سمر (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة / 54 / طفلاً تعرضوا للاختناق حول الولادة، وقبلوا في شعبة الوليد بمشفى الأسد الجامعي باللاذقية في الفترة 4/2004 حتى 4/2005. كانت نسبة هؤلاء المرضى من القبولات ( 16.6%)، ونسبة الذكور إلى الإناث (2 : 1). أكثر عوامل الخطرمشاهدة: 1 - وجود إجهاضات سابقة 35 % من الحالات. 2 - الإنتان البولي أو التناسلي 35 %. 3 - الخداجة 31.5%. ولم تشكل طريقة الولادة عامل خطورة حيث تساوت نسبة الولادات الطبيعية والقيصرية. قسم المرضى حسب شدة الإصابة إلى 3 درجات: - درجة I خفيفة في 22 % من الحالات. - درجة II متوسطة في 48 % من الحالات. - درجة III شديدة في 30 % من الحالات. وجدت الاختلاجات في(44 % ) من الحالات ونقص المقوية في( 73 %) من الحالات. ووجد الحماض عند كل الولدان الذين أمكن معايرة غازات الدم لديهم باكرا" (خلال 30 دقيقة ). وكان ارتفاع عيار CPK المشعر المخبري الأكثر حساسية لنقص الأكسجة بنسبة (94.5 %). وجدت موجودات شعاعية مرضية بالإيكو عبر اليافوخ المجرى باكراً في (37 %) من الحالات، وكذلك شوهدت موجودات مرضية بطبقي الرأس المجرى بعد أسبوع في (37.3 %) من الحالات. وبلغت نسبة الوفيات (27.8 %). أمكن متابعة معظم المرضى بعد التخريج، ووجدت عقابيل عصبية عند (25 %) منهم. و كانت نسبة الخدج من جميع الولدان المتضررين (33.3 % ). Our study, which was performed in AL-ASSAD University Hospital in Lattakia from 4\2004 to 4\2005, included 54 newborn infants who suffered from prenatal Asphyxia. The number of infants was 16.6 % of admissions at incubator department. The male to female ratio was 2 : 1. The most frequent risk factors were - Previous abortions 35 %. - Urogenital infections 35 %. - Prematurity 31.5 %. Cesarean deliveries ratio was equal to vaginal deliveries. So the type of delivery was not a risk factor. The patients were divided to 3 degrees according to severity of injury: - Mild: in 22 % of cases. - Moderate: in 48 %. - Severe: in 30 %. Seizures occurred in 44 % of infants, and 37 % of infants were hypotonic. Acidosis was found in all infants, whose blood gases have got early during 30 minutes. We found out that increasing CPK was the most sensitive laboratory indicator of hypoxia with a rate of 94.5 %. We also found the radio of pathological present in early cranial ultrasound in 37 % of patients, and in cranial C.T done after the first week of life in 37.3 % of patients. Mortality rate was 27.8 %. We could follow-up most of patients after discharge and neural sequelae were found in 25 % of them. 33.3 % of the damaged infants were premature.